Numerical Investigation of the Effect of Using CO2 as the Refrigerant in a Heat Pump Tumble Dryer System - Erdem, Serkan; Heperkan, Hasan (TAYLOR & FRANCIS INC, 2014)
CO2 appears to be a suitable refrigerant for dryer operation conditions due to its thermophysical and environmentally friendly properties. In this study, a heat pump tumble dryer system using CO2 as the refrigerant was theoretically investigated, and a computer model was developed using MATLAB software. The changes in the energy consumption and drying time, depending on the inlet CO2 pressure into the gas cooler, inlet CO2 temperature into the evaporator, air mass flow rate, and dryer efficiency, are presented. The results show that the optimum operating parameters are extremely effective in reducing the drying time and energy consumed.
Keywords: Carbon dioxide; Heat pump dryer; Modeling; Transcritical cycle; CARBON-DIOXIDE; WORKING FLUID; SIMULATION; PERFORMANCE; CYCLES; Engineering